Method for measuring quantum phase noise and working transition line width of radio-optical system of random number generator - Nariezhnii, O.P.; Semenets, V.V.; Grinenko, T.O. (Radiotekhnika, 2018)
Results of comprehensive theoretical and experimental studies on creation of a Quantum Random Number Generator (QRNG) prototype based on the implementation of double radio optical resonance in the vapor of the rubidium isotope are presented. A method is developed for the analytical and numerical solution of the coupled-mode QRNG equation, which describes the mode of interaction of quantum generators in the process of measuring their parameters. A feature of the proposed method is the possibility of studying quantum phase noise and the width of the quantum discriminators line on alkali metal vapors in the presence of an interaction error.